Tinjauan Atas Prosedur Pengelolaan Persediaan Pada Hotel Pesona Alam Resort & Spa - Amanda, Dina; Sudradjat, Sudradjat; Suryanti, Cecilia Valentina Sri Hadi (Jurnal Ilmiah Pariwisata Kesatuan, 2023)
ABSTRACT Inventory is a fairly large current asset and has an important role in every company. Inventory is used to support the company's operational activities. Inventory management activities need to be carried out with correct procedures so that inventory security can be maintained. Security needs to be maintained starting from the purchasing process, storage to the inventory dispensing process. The purpose of this review is to understand how inventory management procedures are implemented at the Pesona Alam Resort & Spa Hotel in order to meet the needs of the company's operational activities. Apart from that, to find out the documents used and related parts in inventory management procedures at the Pesona Alam Resort & Spa Hotel. The results of the review show that inventory management procedures comply with the SOP determined by the company and are also implemented well. There is a separation of duties between related sections and the completeness of the documents is quite good. Keywords: Inventory Management